Daily Intake of Advanced Glycation End Products, Fibers and Vitamin C: Their Relationship with Nutrition Status in Adolescent Girls - Sholichah, Rizka M; Hanim, Diffah; Indarto, Dono (International Journal of Human and Health Sciences (IJHHS), 2020)
Introduction: Eating habits including food choice are responsible formalnutrition problem in Indonesia. For example, fast foods are very popular in adolescent life, especially who lives in urban areas. The objective of this research is to analyze the relationship of daily intake of Advanced Glycation End products (AGEs), fibers and vitamin C with nutrition status in adolescent girls. Methods: This cross sectional study was conducted in 150 adolescent girls of senior high schools who were in grade X and XI in Kediri city, East Java Province. Data of AGEs, fibers and vitamin C intake were determined using a 24h food recall questionnaire for two alternating days.Nutrition status was based on body mass index for age based on the z-score issued by the Indonesian Ministry of Health. The chi square and multiple logistic regression test was used to analyze the relationship of those variables with nutrition status. The significant level was set up at p value < 0.05. Results: The prevalence of overweight and obese was 26% in adolescent girls. Inadequate daily intake of fibers and vitamin C was commonly found in adolescent girls whilst AGEs were highly consumed by adolescent girls. AGEs intake (OR=1.85; 95% CI: 0.88-3.85; p=0.101), fiber intake (OR=0.92; 95% CI: 0.43-1.99; p= 0.839) and vitamin C intake (OR=0.85; 95% CI: 0.36-1.99; p=0.710) were positively related to nutrition status but it was not statistically significant. Discussion: High intake of AGEs and low intake of fiber and vitamin Cincreases the risk of overweight and obese in adolescent girls, compared to those who have low intake of AGEs and high intake of fibers and vitamin C but it was not statistically significant. International Journal of Human and Health Sciences Vol. 04 No. 02 April’20 Page : 109-113